Structural Engineering of Hierarchical Magnetic/Carbon Nanocomposites via In Situ Growth for High-Efficient Electromagnetic Wave Absorption - Liu, Xianyuan; Zhou, Jinman; Xue, Ying; Lu, Xianyong (Nano-micro letters, 2024)
Highlights Hierarchical Fe 3 O 4 -Fe@CNFs/Al-Fe 3 O 4 -Fe nanocomposites were constructed by in situ growth, vacuum-assisted filtration, and self-reduction methods. The carbon framework, with in situ grown magnetic nanoparticles, supports two-dimensional magnetic nanosheets, achieving excellent electromagnetic performance and good impedance matching. Excellent reflection loss value (− 59.3 dB), broadband wave absorption (5.6 GHz at 2.2 mm thickness), and low radar cross-section value were achieved. Materials exhibiting high-performance electromagnetic wave absorption have garnered considerable scientific and technological attention, yet encounter significant challenges. Developing new materials and innovative structural design concepts is crucial for expanding the application field of electromagnetic wave absorption. Particularly, hierarchical structure engineering has emerged as a promising approach to enhance the physical and chemical properties of materials, providing immense potential for creating versatile electromagnetic wave absorption materials. Herein, an exceptional multi-dimensional hierarchical structure was meticulously devised, unleashing the full microwave attenuation capabilities through in situ growth, self-reduction, and multi-heterogeneous interface integration. The hierarchical structure features a three-dimensional carbon framework, where magnetic nanoparticles grow in situ on the carbon skeleton, creating a necklace-like structure. Furthermore, magnetic nanosheets assemble within this framework. Enhanced impedance matching was achieved by precisely adjusting component proportions, and intelligent integration of diverse interfaces bolstered dielectric polarization. The obtain Fe 3 O 4 -Fe nanoparticles/carbon nanofibers/Al-Fe 3 O 4 -Fe nanosheets composites demonstrated outstanding performance with a minimum reflection loss (RL min ) value of − 59.3 dB and an effective absorption bandwidth (RL ≤  − 10 dB) extending up to 5.6 GHz at 2.2 mm. These notable accomplishments offer fresh insights into the precision design of high-efficient electromagnetic wave absorption materials.